SILENE MULTIFLORA IN MOLDOVA (ROMANIA) - Culiţă SÎRBU; Adrian OPREA (Journal of Plant Development)
Silene multiflora, a critically endangered species from the vascular flora of Romania, was first reported in the historical province of Moldova (east of the country) since the first half of the 19th century. However, the presence of this species in Moldova was later on contested (confusion with S. nemoralis or with S. viscosa?), and in the national floristic syntheses published up to now, the species has not been mentioned in the flora of this province. In this work, we confirm the occurrence of the species S. multiflora in northeastern Romania (Moldova), based on the specimens collected in the field, as well as on some older specimens kept in two public herbaria in Iasi.